2014
DOI: 10.1097/hjh.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

The role of autonomic and baroreceptor reflex control in blood pressure dipping and nondipping in rats

Abstract: This study confirms that the sleep-wake cycle is more important than the light-dark cycle in determining BP dipping. Moreover, lower baroreflex control and parasympathetic activity during quiet sleep as well as lower sympathetic activity during active waking are associated with reduced BP dipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Individuals who do not exhibit this blood pressure dipping pattern are called "non-dippers" and are at higher risk for developing kidney and cardiovascular diseases (46). Blood pressure has also been shown to drop Ն10% in rats during their dormant phase (i.e., daytime) (26). We found that MAP did not drop by Ն10% in either SS or SR rats during their dormant phase, regardless of whether or not their (17).…”
Section: Discussionmentioning
confidence: 60%
“…Individuals who do not exhibit this blood pressure dipping pattern are called "non-dippers" and are at higher risk for developing kidney and cardiovascular diseases (46). Blood pressure has also been shown to drop Ն10% in rats during their dormant phase (i.e., daytime) (26). We found that MAP did not drop by Ն10% in either SS or SR rats during their dormant phase, regardless of whether or not their (17).…”
Section: Discussionmentioning
confidence: 60%
“…Autonomic system dysfunction, abnormal neurohormonal regulation, and inflammatory activation are implicated in this perspective . Clinical and experimental studies that investigated the autonomic nervous system dysfunction in AH could provide possible explanations for the observed endothelial dysfunction in nondippers. Sympathetic nervous system alterations, with enhanced sympathetic hyperactivation and consequent increase of vasoconstrictors, observed mainly in nondippers, might explain the endothelial dysfunction that was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the baroreceptor reflex is qualitatively the same across experimental preparations, it is also recognized that the dynamic properties of the response are altered by anesthetics and decerebration (Seagard et al, 1982 , 1983 ; Abdel-Rahman et al, 1987 ; Stornetta et al, 1987 ; Matsukawa and Ninomiya, 1989 ; Suzuki et al, 1993 ; Farber et al, 1995 ; Muzi and Ebert, 1995 ; Ebert et al, 1998 ; Katsuda et al, 2000 ; Lee et al, 2004 ). The baroreceptor reflex is also affected by transitions in sleep/wake and behavioral states and following stress (Stephenson et al, 1981 ; Coote, 1982 ; Conway et al, 1985 ; Del Bo et al, 1985 ; Knuepfer et al, 1986 ; Kasting et al, 1987 ; Mion and Krieger, 1988 ; Sei et al, 1994 ; Vaile et al, 1996 ; Sei and Morita, 1999 ; Zoccoli et al, 2001 ; Kanbar et al, 2007 ; Grippo et al, 2008 ; Julien, 2008 ; Cortelli et al, 2012 ; Almeida et al, 2014 ; Kuo et al, 2014 ). The latter findings highlight an influence of supratentorial brain regions on the brainstem circuitry that regulates SNA and blood pressure.…”
Section: Contributions Of the Midbrain Diencephalon And Telencephalmentioning
confidence: 99%